Teachers’ and Students’ Perception of Animation Video by Animaker in Blended Learning - I Gede Bayu Kartika Yasa (International Journal of English Education and Linguistics (IJoEEL), 2023)
In the post-COVID-19 pandemic era, the learning style of young learners has changed from online learning to blended learning. It means that young learners must adapt to face-to-face and online learning. It also causes the teacher to prepare on how to make effective blended learning, which demands the teacher to prepare the learning material both in face-to-face and online learning. In addition, in teaching young English learners, especially young learners, the learning media used must be exciting and compelling. Currently, the use of animation videos is constructive for young learners during the COVID-19 pandemic because the contents are delivered to keep them learning even if they learn independently. This study aims to delve into the teachers’ and students’ perceptions of the use of animation videos by Animaker as learning media in blended learning in the post-pandemic era. This study used a descriptive qualitative method explained through in-depth interviews with two teachers and ten EFL students in an elementary school. The result explained that audio-visual media in the form of animation videos by Animaker effectively to be used in blended learning. Because the animation videos were attractive, the students were motivated to learn. The implementation was also flexible that could be learned anytime and anywhere. However, some platform limitations, such as limited export time and limited characters used for free users, became a disadvantage. This article is expected to help teachers develop engaging learning media that motivate young learners.